Pengaruh Penanganan Komplain dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada pengguna J&T di Kabupaten Kolaka Utara - Jumriani Jumriani; Fitri Kumalasari; Almansyah Rundu Wonua (CV. ITTC INDONESIA, 2022)
This research aims to determine (1) the effect of complaint handling on customer satisfaction among J&T users in North Kolaka Regency. (2) the influence of service quality on customer satisfaction among J&T users in North Kolaka Regency. The sample in this study amounted to 110 respondents using a sampling technique, namely accidental sampling. Research instrument testing uses validity and reliability tests with SPSS 22.0. The research data analysis technique uses the Structural Equatio Modeling (SEM-PLS) method with SmartPLS 4.0. Based on the results of this research, it can be seen that the complaint handling variable has a positive and significant effect on customer satisfaction as indicated by a T-Statistic value of 3,493 and a P-Value of 0.000, the service quality variable has a positive and significant effect on customer satisfaction as indicated by the T-Statistic value of 4.125 and P-Values ​​of 0.000.